The impact of subclinical congestion on the outcome of patients undergoing transcatheter aortic valve implantation. (15th May 2020) - Adlbrecht, Christopher; Piringer, Felix; Resar, Jon; Watzal, Victoria; Andreas, Martin; Strouhal, Andreas; Hasan, Waseem; Geisler, Daniela; Weiss, Gabriel; Grabenwöger, Martin; Delle‐Karth, Georg; Mach, Markus
Abstract: Background: We investigated the impact of an elevated plasma volume status (PVS) in patients undergoing TAVI on early clinical safety and mortality and assessed the prognostic utility of PVS for outcome prediction. Materials and methods: We retrospectively calculated the PVS in 652 patients undergoing TAVI between 2009 and 2018 at two centres. They were then categorized into two groups depending on their preoperative PVS (PVS ≤−4; n = 257 vs PVS>−4; n = 379). Relative PVS was derived by subtracting calculated ideal (iPVS = c × weight) from actual plasma volume (aPVS = (1 − haematocrit) × (a + (b × weight in kg)). Results: The need for renal replacement therapy (1 (0.4%) vs 17 (4.5%); P  = .001), re‐operation for noncardiac reasons (9 (3.5%) vs 32 (8.4%); P  = .003), re‐operation for bleeding (9 (3.5%) vs 27 (7.1%); P  = .037) and major bleeding (14 (5.4%) vs 37 (9.8%); P  = .033) were significantly higher in patients with a PVS>−4. The composite 30‐day early safety endpoint (234 (91.1%) vs 314 (82.8%); P  = .002) confirms that an increased preoperative PVS is associated with a worse overall outcome after TAVI. Conclusions: An elevated PVS (>−4) as a marker for congestion is associated with significantly worse outcome after TAVI and therefore should be incorporated in preprocedural risk stratification.